The Effect of Celebrity Endorsement and Sosial Media Marketing on Purchase Intention Skincare Product in Tiktok Shop - Atmaja, Dodi Ria; Rahayu, Pungky (Majalah Ilmiah Bijak, 2023)
Sosial media has become a place for many people to interact. Almost everyone, from young to old, uses Sosial media. Communicating and shopping as activities that can be done online, the presence of Sosial media provides benefits for users to provide convenience and keep abreast of the development of increasingly modern Sosial media. The purpose of this study is to analyze the effect of Sosial media marketing, celebrity endorsements, and brand image on purchase intention. This study uses the Structural Equation Model Partially Least Square (SEM-PLS) method and the purposive sampling method. The sample taken from this study consisted of 107 respondents who met the criteria that they had shopped for skincare through the Tiktok shop. Data analysis testing using SmartPLS The results of this study prove that celebrity endorsement has a positive effect on purchase intention; the indirect relationship between Sosial media marketing and purchase intention is mediated by brand image; brand image has a positive effect on purchase intention; Sosial media marketing has no effect on purchase intention; and celebrity endorsement has no effect on purchase intention mediated by brand image.